PhInd—Database on Polyphenol Content in Agri-Food By-Products and Waste: Features of the Database - Nemanja Teslić; Milica Pojić; Alena Stupar; Anamarija Mandić; Branimir Pavlić; Aleksandra Mišan (Antioxidants, 2024)
Timely access to topic-relevant datasets is of paramount importance for the development of any successful strategy (food waste reduction strategy), since datasets illuminate opportunities, challenges and development paths. PhInd is the first comprehensive database on polyphenol content in plant-based by-products from the agri-food sector or the wastewater sector and was developed using peer-reviewed papers published in the period of 2015–2021. In total, >450 scientific manuscripts and >6000 compound entries were included. Database inclusion criteria were polyphenol contents = determined using HPLC/UHPLC quantitative methods. PhInd can be explored through several criteria which are either ‘open’ or checkboxes. Criteria are given in subsections: (a) plant source; (b) by-product industrial processing; (c) pre-treatment of by-products before the isolation of polyphenols; and (d) the extraction step of polyphenols. Database search results could be explored on the website directly or by downloading Excel files and graphs. This unique database content is beneficial to stakeholders—the food industry, academia, government and citizens.